Integrity, Pride and Love as Power in Jane Austen's Novel: Pride and Prejudice - Ratna Trihartanti; Sri Dewiyanti; Muhammad Yazidus Syukri; Siti Yuliah (Faculty of Language and Literature, University of Surakarta, 2023)
This study aims to find out that relative power (P) variables are not only social status, age, education and wealth. Another aim is to show that negative politeness strategies do not always belong to someone with higher social power. Relative power is one element of social variables that decides politeness strategies. Pride and Prejudice reveal that integrity, pride and love are also variables of relative power. They can also prove that though someone’s social status is not high and her social distance from another participant is asymmetric, she could have power over someone with higher social status. Power characterized by integrity, pride, belief, and freedom from being dominated is called personal power; meanwhile, it is a power determined by a good personality, attractive physical appearance, and referent power. This study uses a qualitative method, and the data is mainly from Pride and Prejudice. The main character of Pride and Prejudice shows us that integrity, pride, and love could be the variables of power deriving from Personal and Referent power. Those powers could develop and deepen relative power in social variables to be applied in politeness studies.